MyPyramid Message: Variety - Claudia Peñuela; Emily Minton (EDIS)
FCS8927, a 2-page handout by Claudia Peñuela and Emily Minton, explains how variety is represented in the MyPyramid symbol, why variety is important, and provides tips for eating a variety of foods. Includes a review exercise and references. Published by the UF Department of Family, Youth and Community Sciences, October 2010.